Effect of Oral Docosahexaenoic Acid (DHA) Supplementation on DHA Levels and Omega-3 Index in Red Blood Cell Membranes of Breast Cancer Patients - Molfino, Alessio; Amabile, Maria I.; Mazzucco, Sara; Biolo, Gianni; Farcomeni, Alessio; Ramaccini, Cesarina; Antonaroli, Simonetta; Monti, Massimo; Muscaritoli, Maurizio (Frontiers in Physiology, 2017)
Rationale: Docosahexaenoic acid (DHA) in cell membrane may influence breast cancer (BC) patients' prognosis, affecting tumor cells sensitivity to chemo- and radio-therapy and likely modulating inflammation. The possibility of identifying BC patients presenting with low DHA levels and/or low ability of DHA incorporation into cell membrane might help to treat this condition. Methods: We enrolled BC patients and healthy controls, recording their seafood dietary intake. DHA in form of algal oil was administered for 10 consecutive days (2 g/day). Blood samples were collected at baseline (T0) and after 10 days of supplementation (T1) to assess DHA, omega-3 index, as the sum of DHA + eicosapentaenoic acid (EPA), in red blood cells (RBC) membranes and plasma tumor necrosis factor-alpha and interleukin -6 levels. Pre- and post-treatment fatty acid profiles were obtained by gas-chromatography. Parametric and non-parametric tests were performed, as appropriate, and P value <0.05 was considered statistically significant. Results: Forty-three women were studied, divided into 4 groups: 11 patients with BRCA1/2 gene mutation (M group), 12 patients with familiar positive history for BC (F group), 10 patients with sporadic BC (S group), and 10 healthy controls (C group). DHA and omega-3 index increased from T0 to T1 in the 3 groups of BC patients and in the controls (P<0.001). No difference was found in DHA incorporation between each group of BC patients and between patients and controls, except for M group, which incorporated higher DHA levels with respect to controls (beta=0.42; P=0.03). No association was documented between cytokines levels and DHA and omega-3 index at baseline and after supplementation. Independent by the presence of BC, women considered as “good seafood consumers” showed at baseline DHA and omega-3 index higher with respect to “low seafood consumers” (P=0.04; P=0.007, respectively). After supplementation, the increase in DHA levels was greater in “low seafood consumers” with respect to “good seafood consumers” (P<0.0001). Conclusion: DHA supplementation was associated with increased DHA levels and omega-3 index in RBC membranes of BC cancer patients, independent of the type of BC presentation, and in controls. BRCA1/2 mutation, as well as low seafood consuming habits in both BC.